Student mental health & wellbeing in higher education a practical guide - Barden, Nicola; Caleb, Ruth (London SAGE Publications, 2019)
Good mental health is essential for students to manage the challenges that university life presents. This book offers pragmatic guidance to support academic and student services staff in engaging with this critical issue, both in terms of being proactive within their role to promote a positive approach to wellbing, and understanding how to care appropriately for students who may not be flourishing in the university environment--
Part I. The Context : 1. Higher education in the twenty-first century: Changes and challenges for mental wellbing / Ruth Caleb and Nicola Barden -- 2. The legal position: Obligations and limits / Siân Jones-Davies -- Part II. Mental Health : 3. Student mental health and the developing mind / Dominique Thompson -- 4. The student lifecycle: Pressure points and transitions / Denise Meyer -- 5. Cultural approaches to mental health among migrating students / Antonio Ventriglio, Gurvinder Kalra and Dinesh Bhugra -- Part III. Policy and Practice : 6. From strategy to policy and procedure: Making mental health policies work / Ruth Caleb -- 7. Academic and departmental support / Ann-Marie Houghton -- 8. Professional support in higher education / Nic Streatfield -- 9. Risk and crisis: Managing the challenges / Nicola Barden -- 10. Supporting staff: Creating the conditions for confident support / Andrew Reeves -- Conclusion / Nicola Barden & Ruth Caleb
Includes bibliographical references and index.
Keywords: College students -- Mental health; College students -- Mental health services; Education, Higher -- Psychological aspects; Well-being.; Mental health; Students -- Psychology; Mental health services; School mental health services